THE EFFECT OF THINK-TALK-WRITE (TTW) STRATEGY ON STUDENTS’ WRITING SKILL IN RECOUNT TEXT OF THE TENTH GRADE STUDENTS’ OF SMA SWASTA PELITA BULU CINA - Ida Nova; Ummi Umara; Sri Ulina Beru Ginting (STKIP Budidaya Binjai, 2022)
The object of the study was to find out whether there was an effect of think-talk-write (ttw) strategy on students’ writing skill in recount text. The research design in this study was quasi-experimental design by using pre-test and post-test. This study was conducted with the tenth grade students of SMA Swasta Pelita Bulu Cina as the population of the study . The sample with 60 students as the sample of this study. The writer used X IPA-1 which consist of 30 students as the experimental class and X IPA-2 which consist of 30 students as the control class. The writer used test as the instrument of collecting data. The data collected from this study were analyze using t-test formula. The result of this study that was a positive effect of the result students’ writing skill in recount text after using think-talk-write (ttw) strategy. It can be seen from the data analysis, it was found that value of t-observed (to) was higher than t-table (tt). The result from calculating the data was t-observed (to= 16,48) and t-table (tt= 1.67), it means, to is higher than tt in significant level 5% so the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. In order words, using think-talk-write (ttw) strategy had effect on students’ writing skill in recount text of the tenth grade students of SMA Swasta Pelita Bulu Cina in academic year 2021/2022.